Manajemen Resiko Pembiayaan pada Bank Syariah: Suatu Tinjauan Filsafati - Iskandar Iskandar; Amiur Nuruddin; Saparuddin Siregar (Al-Ulum, 2017)
This article is a continuation of the discourse on the concerns and dilemmas of the development of Islamic banking among the financing of profit sharing with the mark-up system (murabah). This study attempts to explain the reasons for saturation of sharia banks in financing the profitsharing. It aims to present the principles of risk-sharing financing management and also strive to offer its philosophical construction. Funding risk management principles in sharia banks should refer to the principle of tauhid. On the basis of these basic principles, general principles of risk management of musharaa are ibnÄdah, ibÄah, freedom of contract, consensus, principles of engagement, principles of equilibrium and partnership, benefit, trust, justice, democracy and, fath aÅ¼-Å¼arÄ«ah. These principles are based on four conscious awareness risk, should not direct itself in loss (wa la tulkuu), awareness on the obligation to do good deeds (wah ahshinu) and transcendental awareness (wa-takuw).